Impact of tea leaves categories on physicochemical, antioxidant, and sensorial profiles of tea wine - Zou, Chun; Chen, De-Quan; He, Hua-Feng; Huang, Yi-Bin; Feng, Zhi-Hui; Chen, Jian-Xin; Wang, Fang; Xu, Yong-Quan; Yin, Jun-Feng (Frontiers in Nutrition, 2023)
Tea is the main raw material for preparing tea wine. In this research, four types of tea wine were prepared using different categories of tea leaves, including green tea, oolong tea, black tea, and dark tea, and the comparative study looking their physicochemical, sensorial, and antioxidant profiles were carried out. The dynamic changes of total soluble solids, amino acids and ethanol concentrations, and pH were similar in four tea wines. The green tea wine (GTW) showed the highest consumption of total soluble solids and amino acids, and produced the highest concentrations of alcohol, malic, succinic, and lactic acid among all tea wines. The analysis of volatile components indicated the number and concentration of esters and alcohols increased significantly after fermentation of tea wines. GTW presented the highest volatile concentration, while oolong tea wine (OTW) showed the highest number of volatile compounds. GTW had the highest total catechins concentration of 404 mg/L and the highest ABTS value (1.63 mmol TEAC/mL), while OTW showed the highest DPPH value (1.00 mmol TEAC/mL). Moreover, OTW showed the highest score of sensory properties. Therefore, the types of tea leaves used in the tea wine production interfere in its bioactive composition, sensorial, and antioxidant properties.